Review of 20-year results of ASCOT Legacy - M. B. Nagorny; A. N. Kuchmin (Российский кардиологический журнал, 2023)
The article presents the results of a 20-year follow-up of patients in the ASCOT Legacy study, indicating that antihypertensive and lipid-lowering therapy reduces mortality in patients with hypertension and high cardiovascular risk in the long term. In the group of patients treated with amlodipine compared with the β-blocker atenolol, there was a decrease in mean systolic and diastolic blood pressure (BP), as well as a long-term improve in the form of a decrease in the prevalence of cardiovascular events and mortality due to stroke. An important feature of therapy based on amlodipine was the reduction in BP variability. The article reflects the results of major studies that determine the possibility and effectiveness of early prescription of combined antihypertensive and lipid-lowering therapy.